Experimental basic factors in the production of H2 via supercritical water gasification - Ferreira-Pinto, Leandro [UNESP]; Silva Parizi, Marcela Prado [UNESP]; Carvalho de Araújo, Paulo Cardozo; Zanette, Andreia Fatima [UNESP]; Cardozo-Filho, Lucio (Elsevier, 2019)
This study aims to discuss some of the factors that influence the production of hydrogen via the gasification of organic matter in supercritical water. These factors have been investigated based on the reactions of organic matter with relatively simple chemical structures, such as ethanol, glycerol, and glucose. Investigations of these relatively simple organic materials demonstrate the characteristics and trends in the gasification in supercritical water. The results reported in the literature for these organic compounds can also be extrapolated to the reactions of biomass containing ethanol, glucose, (sugar cane industry) and glycerol (biodiesel industry) in supercritical water. Many organic compounds with different levels of molecular complexity can be used to produce hydrogen, which represents an interesting form of energy storage. Supercritical water (Tc ≥ 374 °C, Pc ≥ 22.1 MPa) has unique physical and chemical properties that minimize mass transport limitations, making it an excellent medium for the decomposition of organic compounds. Thus, understanding the key factors that influence organic compound gasification in supercritical water is extremely important. In this study, we summarize some of the key factors involved in these reactions. The main experimental factors were confirmed to be the temperature, concentration of organic matter in the feed, space time/feed rate, catalysts, oxidants, material and design of the reactor, and pressure. In addition, operational challenges, namely, catalyst deactivation and corrosion are mentioned in the text. Furthermore, the operational challenges were discussed, and the state of the art regarding the gasification of ethanol-, glycerol-, and glucose-containing biomass is also presented.
Keywords: Gasification; Hydrogen; Review; Supercritical water